Anti-Allergic and Antioxidant Activity of 5-Hydroxy-3,6,7,3’,4’- Pentamethoxy Flavone Isolated from Leaves of Vitex negundo - I. Patel, Jignesh; S. Deshpande, Shrikalp (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2011)
Objectives: Bioactivity guided fractionation of leaves of Vitex negundo for their anti-allergic and antioxidant activity and structure elucidation of active fraction responsible for these activities. Methods: Ethyl acetate fraction of leaves of Vitex negundo was fractionated into aqueous sub fraction, acetone sub fraction and chloroform sub fraction according to possible separation of chemical spots present in ethyl acetate fraction using thin layer chromatography and developed solvent system. Anti-allergic activity of aqueous sub fraction, acetone sub fraction and chloroform sub fraction was carried out using homologous passive cutaneous anaphylaxis model in rat. Antioxidant activity of aqueous sub fraction, acetone sub fraction and chloroform sub fraction was carried out using egg albumin induced oxidative stress in guinea pigs. Various spectroscopy methods like Ultraviolet-visible (UV) spectroscopy, Fourier-transform infrared (FT-IR) spectroscopy, Electron impact (EI)-Mass spectroscopy and Proton nuclear magnetic resonance (H1 NMR) spectroscopy were used to determine structure of active sub fraction of leaves of Vitex negundo that possesses anti-allergic and antioxidant activity. Results: Aqueous sub fraction produced significant lesser amount of dye leakage at 200 mg/kg (1.6648±0.0372; p<0.001), when compared with the control group (4.0094±0.2474; p<0.001). Animals treated with aqueous sub fraction showed significantly higher superoxide dismutase (SOD) activity, catalase activity and reduced glutathione level and lower malondialdehyde (MDA) level as compared to untreated sensitized animals. Structure of aqueous sub fraction was determined as a 5-hydroxy- 3,6,7,3’,4’-pentamethoxy flavone. Conclusion: Aqueous sub fraction of leaves of Vitex negundo possesses anti-allergic and antioxidant activity. It is identified as a 5-hydroxy-3,6,7,3’,4’-pentamethoxy flavone. It may be useful in the treatment of various allergic and immunologic diseases and to prevent oxidative stress in many diseases like cancer, liver injury, cardiovascular disease, asthma etc.
Keywords: Allergy